Indicators and instruments to assess components of disability in community-dwelling older adults: a systematic review - Moreira, Juliana Santos (2022)
The epidemiological demands of aging point to the need for characterizing older adults regarding health and disability. This systematic review aims to summarize the indicators (instruments) identifying different components of disability as a result of aging exposition in community-dwelling older adults, considering the International Classification of Functioning, Disability, and Health framework. Taking the PRISMA 2020 recommendations as a reference, studies with community-dwelling older adults, reporting the development and/or age disability modifications were included. Two reviewers analyzed the observational studies searched in the MEDLINE, CINAHL, Web of Science, Scopus, and Embase databases. Of the 137 potentially eligible studies, 49 were included in this review. Several indicators (instruments) demonstrated older adults’ disabilities according to the different domains of the ICF. Objective measures assessed Body Structures, Body Functions, and Environmental Factors and included handgrip strength (dynamometry, n = 8), cognitive function (Mini-Mental State examination, n = 7), gait speed (walk test, n = 6), and endurance (Chair stand-test, n = 4). Self-reported measures assessed Activities and Participation, but not the Body Structures, and included the basic and instrumental activities of daily living (ADL) (the Katz Index of ADL, n = 4 studies, the Lawton and Brody Instrumental ADL, n = 4 studies). The summary of the measures gathered can guide researchers and health professionals to select indicators (instruments) to assess and monitor older adults’ disabilities resulting from aging exposition, to support the development of new wearables, and to provide improvements to the existing ones, allowing the tailored assessment of different health and disability dimensions.